Students’ Strategies and Challenges to Understand Materials in Asynchronous Learning - Kurniawati, Dewi; Mardiningrum, Arifah (Universitas Muhammadiyah Yogyakarta, 2022)
Pandemic in Indonesia makes people in the education environment have to do learning from home, and students must do online learning. Asynchronous learning is one of the learning methods used in education as learning from home. This study aims to know the students' strategies and challenges in implementing the strategies in understanding the material in asynchronous learning. This study uses a descriptive qualitative design. To collect the data using an interview with six participants from the English Language Education Department at one of the private universities in Yogyakarta. The researcher found nine strategies used by students: reading the material, looking for additional material, making a note, watching the video, learning independently, studying together, translating the material, asking the friend and the teacher, and boosting the mood. There are five challenges that students face when implementing the strategies, namely, exhaustion, difficulty in comprehension, lack of confidence, absence of help, and mood swing.